Ecovillages and Transition Towns: Practices of Sustainable Settlements in Urban and Rural Austria - Ozge Yalciner Ercoskun; Anna Kajosaari; Alois Humer (Land)
This study investigates sustainable settlements—in terms of low-carbon settlements and communities transitioning from oil dependence to local resilience—in urban and rural areas of Austria. The objectives of this study are twofold: First, to examine the Global Ecovillage Network (GEN) and Transition Towns Network (TTN) as platforms for alternative lifestyles for urban and rural planning and, second, to comprehend the socio-spatial factors influencing the development of future transition settlements. This study provides updated insights into the concepts of the Global Ecovillage Network in a rural context as well as transition culture in an urban context. In two case studies, we focus on one Global Ecovillage Network (GEN) member, the Cambium Ecovillage near the village of Fehring, Styria, and one Transition Town Network member, Graz, the capital city of Styria. Using transdisciplinary and participatory methodologies, we examine the specific local contexts of these sustainable settlements. Ultimately, the findings of the study about facilitating participatory land use frameworks can be extrapolated from the Austrian context to the broader European context. Conclusions drawn from the results will inform potential future urban and rural land use initiatives concerning ecovillages and transition towns across Europe.